Water quality characteristics in different mangrove disturbance levels, Matang Mangrove Forest Reserve, Peninsular Malaysia - Nik Zaidin, Nik Harun Al-Rashid; Abu Bakar, Siti Nurhidayu; Ahmad Shafuan, Mohammad Faizalhakim; Gandaseca, Seca; Mohamad Kasim, Mohamad Roslan; Abdul Malek, Ismail Adnan (2015)
Mangrove forests playing significant role in local economic generation especially for fisheries and charcoal products. The ecosystem services by mangrove areas are includes carbon absorption and shoreline protection. Variation in hydrological characteristics might be influenced by climate change which affects the extreme events and climate cycles. Uncontrolled land conversion and poor land use management resulted excessive pollution that might affect mangrove health. The growth and composition of mangrove communities are affected by temperature, soil types, salinity, duration and frequency of inundation, accretion of silt, tidal and wave energy and such aperiodic factors as cyclone or flood frequencies. The Matang Mangrove Forest Reserve (MMFR) is a large contiguous mangrove forest area in Peninsular Malaysia (40,466ha). The aerial images were used to classify the different mangrove disturbance levels (e.g. least disturbed, moderately disturbed and mostly disturbed) and relates the conditions with water quality data. Water quality data from 2004 to 2013 were acquired from Department of Environment (DOE). The variation of annual water quality characteristics were analyzed in relation to the classification of mangrove disturbance levels. The findings indicates that three mangrove areas have different disturbance level, and from the water quality analysis, Kuala Trong was least disturbed, Sungai Kerang was moderately disturbed and Kuala Sepetang was mostly disturbed area. These findings will be used to facilitate meteorological, discharge and water quality data collection and analysis for hydrological standards development for mangrove forest in future.